Osteosarcopenic obesity in cardiovascular patients. Controversial and open issues - K. E. Krivoshapova; V. L. Masenko; E. D. Bazdyrev; O. L. Barbarash (Кардиоваскулярная терапия и профилактика, 2021)
See “Inflammaging in the pathogenesis of chronic non-communicable diseases”, Kim O. T. in Opinion of invited editor, pp. 54-55.The study of osteosarcopenic obesity (OSO) in patients with cardiovascular diseases (CVDs) in recent years has caused a dis-cussion on common pathogenesis of atherosclerosis, obesity, progressive loss of skeletal and muscle mass. Are these processes independent age-related conditions or comorbidities with common links of pathogenesis? The aim of this review was to analyze studies on OSO in patients with CVDs. We used following electronic databases: PubMed, Clinical Trials, Google Scholar, www.elibrary.ru. Based on this analysis, modern ideas on the etiology, epidemiology and pathogenesis of OSO in elderly and senile patients with atherosclerosis were described. The authors concluded that absence of standards for OSO diagnosis and inadequate clinical suspicion of specialists during routine examination is one of the main causes of its insufficient detection in elderly patients with CVDs. The results of analyzed studies allow us to consider the OSO and atherosclerotic changes as a single link of cardiovascular continuum. Eliminating the negative effect of chronic inflammation on human body should be considered as a key mechanism in the treatment of OSO and atherosclerosis. However, more research is needed in this area.